44 Multi-vessel PCI in STEMI after the PRAMI trial: the Irish experience. (28th September 2016) - Cuddy, S; Sullivan, V; Mellotte, G; Yearoo, I; Maree, A; Murphy, R; Cosgrave, J
Abstract : Prior to the publication of the PRAMI trial the guideline recommendation was to only undertake culprit vessel PCI at the time of Primary PCI (PPCI) in the management of ST elevation myocardial infarction (STEMI). The guidelines advocated a staged PCI approach. The benefit of non-culprit PCI at the time PPCI is now widely accepted in the post PRAMI era. We reviewed all patients that underwent PPCI for STEMI in St James in 2015 to examine our practice in this regard. We recorded the number of patients that underwent multi-vessel PCI (MVPCI) at the time of infarct artery PCI compared with the group that underwent staged PCI and those referred for CABG. We looked at different parameters that may affect decision-making at the time of PPCI such as primary operator and 'on-call hours' to see if these variables influenced the decision to proceed or wait. Patient mortality and length of stay (LOS) were also compared between the groups. We used the Code STEMI database and HIPE data to identify our patient cohort, with review of the patient chart to verify missing details. In 2015 there were 487 patients diagnosed with a STEMI in SJH or transferred to St James as part of the National ACS programme (average age 62.2 years (range 23–91), 25% female). There were 407 (83.6%) patients with a confirmed diagnosis of STEMI, either clinically or angiographically (average age 62.4 years, 25% female). 375 (77%) had PPCI (average age 61.5 years, 23% female). 53 patients had MVPCI at the same time as PPCI (14%, average age 61, 21% female). 58 had staged PCI (15%, average age 62, 17% female); 18 as an inpatient, 36 as an outpatient and for 4 patients it was recommended on repatriation to a PCI centre. LOS in those not repatriated to their local hospital was 8.4 days (median 6.8, range 4.4–17.7) in MVPCI and 8.3 (median 6.3, range 3.3–26.2) in the staged PCI group. The MVPCI group had an inpatient mortality of 3.7% (2 patients), there were no recorded deaths in staged PCI subgroup. The majority of all the cases were performed during 'on-call hours'; MVPCI 64.5% and staged 61.4%. Out of 10 primary operators only one displayed a statistically significant preference for MVPCI versus staged PCI (p < 0.01), and one the opposite (p = 0.01). We referred 17 patients for CABG, 8 having no intervention prior to CABG, 9 following POBA or PCI. In the largest Irish PPCI centre we found the number of patients undergoing non-culprit vessel PCI at the time of PPCI is much larger than those undergoing inpatient staged PCI. There was no reduction in length of stay in our cohort. The prolonged LOS and the mortality rate may reflect the more complex disease in the cohort undergoing MVPCI and also reflect that this is real-life data including patients in cariogenic shock and post cardiac arrest.